A study on staff awareness of Labuan construction industries towards 4R techniques / Azzizul Ambran - Ambran, Azzizul (2011)
The purpose of this study is to identify the level of staff awareness and respond from staff of Construction Industries in Labuan Federal Territory towards the 4R Techniques. Questionnaires were distributed to 150 respondents of Construction Industries located in Jalan Patau-Patau Labuan. This research paper applied the non-probability sampling technique for convenience to gather data. The sampling size of 150 respondents is considered a representative of total population of the respondent. Analyses of data were conducted by using the Statistical Packages for Social Science (SPSS) software to determine whether the output meet its original objectives. The analysis show that most of respondents aware of 4R Techniques as one of reaching out initiatives initiated by Jabatan Alam Sekitar. In addition, the analysis also show that construction staff are practicing 4R Techniques at workplace. Lastly, it show most staff believe that the flyers are effective and will increase the awareness about 4R Techniques.